Sample Preparation of Pharmaceutical Dosage Forms Challenges and Strategies for Sample Preparation and Extraction - Nickerson, Beverly (Springer US : Imprint: Springer, 2011)
Designed as a resource guide for analytical scientists working in the pharmaceutical industry, this comprehensive guide is focused entirely on sample preparation and extraction of pharmaceutical dosage forms.    This book is divided into four parts: •          Part One covers dosage form and diluent properties that impact sample preparation of pharmaceutical dosage forms and the importance of sampling considerations in generating data representative of the drug product batch.  •          Part Two reviews specific sample preparation techniques typically used with pharmaceutical dosage forms. •          Part Three discusses sample preparation method development for different types of dosage forms including addressing drug excipient interactions and post extraction considerations, as well as method validation and applying Quality by Design (QbD) principles to sample preparation methods.   •          Part Four examines additional topics in sample preparation including automation, investigating aberrant potency results, green chemistry considerations for sample preparation and the ideal case where no sample preparation is required for sample analysis.   Analytical scientists in the pharmaceutical industry as well as in analytical testing laboratories will find this book a valuable resource in developing and troubleshooting sample preparation methods for drug products at all stages in the lifecycle of a drug product. Beverly Nickerson, Ph.D., is Associate Research Fellow in Analytical Development in Pfizer Global Research and Development, Pfizer Inc.  Dr. Nickerson is well published in peer-reviewed journals, is author of several book chapters and has presented at various scientific meetings.  She has extensive experience in early stage and late stage drug development.